The Effectiveness Of Village Microfinance Financing Program By Baznas In Encouraging The Development Of Micro-Entreprises - Jasri, Jasri; Wahdah, Andi Syarifah; Malik, Abdul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research aims to identify how the implementation of the village microfinance program by Baznas affects the development of micro-enterprises owned by the beneficiaries in BAZNAS Maros Regency. The research methodology employed in this study involves a qualitative approach with a descriptive nature. Data collection methods include observations, face-to-face interviews, and documentation. The research findings reveal that the execution of the Village Microfinance program by the National Zakat Agency in Maros Regency significantly contributes to micro-entrepreneurs in enhancing their businesses, especially those facing difficulties in accessing capital. The program also assists micro-entrepreneurs in mitigating the decreased income impacts caused by the COVID-19 pandemic. In addition to financial support, beneficiaries entering the micro-business sector also receive market access support from the BAZNAS Village Microfinance program, aiding them in promoting their commercial products more effectively.